Clearance of building of a former uranium concentrates plant. (1st September 2021) - Vico, A.M.; Noguerales, M.C.; Rodríguez, L.; Álvarez, A.
Highlights: Adaptation of MARSSIM methodology from a conservative point of view. Application to a former Uranium concentrates production pilot plant. The results show compliance with the radiological criteria. Abstract: The decommissioning is the last stage in the shelf-life period of any nuclear or radioactive facility. The goal is the controlled removal of the source term in a way that the future use of the buildings decommissioned does not entail any radiological risk for both people and environmental according to a radiological criteria regulator approved. MARSSIM is the methodology followed by many countries to demonstrate compliance with these radiological criteria. This paper describes the adaptation of the MARSSIM methodology to demonstrate compliance of radiological criteria established by European Commisión recommendation (trivial dose equal to 10 µSv·y −1, (Comision for European Communities, Radiation Protection 113. Recommended radiological protection criteria for the clearance of buildings and building rubble from the dismantling of nuclear installations, Luxembourg: Office for Official Publications on the European Communities, 2000 ). Particularly, it has been applied to a former U concentrate facility located in the heart of Madrid (Spain), at the site known today as CIEMAT. The obtained results guarantee that demolition rubbles can managed as non-radiactive waste and that there are not any radiological risk for people in case of building reuse.